The role and impact of Zootaxa in mammalogy in its first 20 years - Cordeiro-Estrela, Pedro; Feijó, Anderson; Gaubert, Philippe; Weksler, Marcelo; Hautier, Lionel; Velazco, Paúl M.; Teta, Pablo; Fabre, Pierre-Henri; Veron, Geraldine; Braun, Janet K. (Zootaxa, 2021)
Zootaxa came as a new and innovative publication medium for taxonomy, amidst a scenario of devaluation of this important biological science. After 20 years, it has ascertained itself as one of the main journals in animal taxonomy. However, the contribution of the journal to the taxonomy of Mammalia (mammals), one of the most studied groups of animals with a long-standing, dedicated spectrum of specialized journals (mammalogy), could have been expected as minor. All the current and former editors of the Mammalia section of Zootaxa analyzed the relative contribution of the journal to the description of new species of mammals since 2001. We also analyzed the contribution of Zootaxa by taxon, geographic origin of taxa, and geographic origin of first authors. The taxonomic methodology of authors in species description is described as well as the temporal trends in publications and publication subjects. We highlight the editors’ picks and eventually, the challenges for the future. We found that Zootaxa has had a significant contribution to mammalogy, being the second journal (the first being Journal of Mammalogy) in terms of number of new species described (76; 10.6% of the new mammalian species described between 2001 and 2020). The majority of the new species were described following an integrative taxonomic approach with at least two sources of data (86%). The analysis of published taxa, their geographic origin, and the country of origin of first authors shows a wide coverage and exhaustive representation, except for the species from the Nearctic. We conclude that Zootaxa has likely responded to a repressed demand for an additional taxonomic journal in mammalogy, with as possible appeals the absence of publication fees and an established publication speed. With 246 articles published in the past 20 years, the Mammalia section of Zootaxa embraces a large spectrum of systematic subjects going beyond alpha taxonomy. The challenges for the future are to encourage publications of authors from the African continent, still poorly represented, and from the palaeontology community, as the journal has been open to palaeontology since its early days.